Farm Operations and Injury Risks to Children in Cocoa Households in the Western Region of Ghana: Implications for Extension Education - Ernest L. Okorley (Journal of International Agricultural and Extension Education, 2017)
Cocoa remains the most important cash crop in Ghana, with the Western Region being the leading producer. More recently, concerns have been raised about ethical cocoa production, especially regarding child labour. Drawing on historical sources and a survey, the research assessed the injury risks of children in cocoa farming in the Western Region of Ghana and its implications for extension education. The study concludes that cocoa farm households in Ghana, typically in Western Region, engage children in the households in almost all aspects of cocoa production operations as a way of socializing them into the family cocoa production business – a complex and socially tolerable practice in Ghana. The extent of engagement however, is low across the operations. The operations engaged by the children are generally repetitive and include carrying loads, land preparation, planting, fertilizer application, harvesting, and breaking cocoa pods. More importantly, the study concludes that cocoa farmers are more at risk to injuries caused by repetitive strain, and lifting and carrying of loads, which are the work normally done by children. Nonetheless, the focus of extension education in Ghana has been on adult farmers in design and content. To effectively manage the risk associated with this complex phenomenon, the study emphasized the need for a holistic extension education that includes child-sensitive labour practices in cocoa production, focusing on the entire farm household. This will best empower cocoa households to ethically and health-wise socialise children as part of a livelihood system for sustainable cocoa production
Keywords: Cocoa production; child labour; Extension education; Ghana; injury risk.